Large-Scale Variability of Inpatient Tacrolimus Therapeutic Drug Monitoring at an Academic Transplant Center: A Retrospective Study. Issue 4 (August 2018) - Strohbehn, Garth W.; Pan, Warren W.; Petrilli, Christopher M.; Heidemann, Lauren; Larson, Sophia; Aaronson, Keith D.; Johnson, Matt; Ellies, Tammy; Heung, Michael
Abstract : Background: Inpatient tacrolimus therapeutic drug monitoring (TDM) lacks standardized guidelines. In this study, the authors analyzed variability in the preanalytical phase of the inpatient tacrolimus TDM process at their institution. Methods: Patients receiving tacrolimus (twice-daily formulation) and tacrolimus laboratory analysis were included in the study. Times of tacrolimus administration and laboratory study collection were extracted, and time distribution plots for each step in the inpatient TDM process were generated. Results: Trough levels were drawn appropriately in 25.9% of the cases. Timing between doses was consistent, with 91.9% of the following dose administrations occurring 12 ± 2 hours after the previous dose. Only 38.1% of the drug administrations occurred within 1 hour of laboratory study collection. Tacrolimus-related patient safety events were reported at a rate of 1.9 events per month while incorrect timing of TDM sample collection occurred approximately 200 times per month. Root cause analysis identified a TDM process marked by a lack of communication and coordination of drug administration and TDM sample collection. Extrapolating findings nationwide, we estimate $22 million in laboratory costs wasted annually. Conclusions: Based on this large single-center study, the authors concluded that the inpatient TDM process is prone to timing errors, thus is financially wasteful, and at its worst harmful to patients due to clinical decisions being made on the basis of unreliable data. Further work is needed on systems solutions to better align the laboratory study collection and drug administration processes. Abstract : Supplemental Digital Content is Available in the Text.